Intellectual and historical background of Western civilization and its impacts (Salam International Academic Journal, 2011)
This research paper dealt with the historical and intellectual background of Western civilization, also addressed the circumstances in which Western civilization has arisen, and stated that this civilization originated as a reaction to distorted Christianity, which was in control of Europe in the Middle Ages, and that the Christianity of the Middle Ages is not the Christianity brought by Jesus; it was Christianity that had been distorted by Paul, along with many other factors and reasons.    And that distorted Christianity, which was based on people's opinions and ideas (and not based on Wahi), cannot keep pace with scientific progress and intellectual development. From here, it opposed any progress in the field of science and philosophy, tried to muzzle the minds of the people, and tried to tyrannize the scientists and philosophers. And when the intellectuals and scientists rejected submission to the rule of the Church, the Church exercised against them all kinds of injustice and abuse.    And when the oppression and assault of the Church increased and exceeded the limits, Europeans blew up at once against it, and instead of taking this position against the distorted Christianity only, they made it a war on the absolute religion and against the commitment to religion; thus, Europe started to fall into the swamp of atheism.
Keywords: Western civilization; historical background; distortion; Inquisition courts; Christianity